2017
DOI: 10.1371/journal.pone.0178259
|View full text |Cite
|
Sign up to set email alerts
|

An inactivated hand-foot-and-mouth disease vaccine using the enterovirus 71 (C4a) strain isolated from a Korean patient induces a strong immunogenic response in mice

Abstract: Enterovirus 71 (EV71) is a major causative agent of hand-foot-and-mouth disease (HFMD) frequently occurring in children. HFMD induced by EV71 can cause serious health problems and has been reported worldwide, particularly in the Asia-Pacific region. In this study, we assessed the immunogenicity of a formalin-inactivated HFMD vaccine using an EV71 strain (FI-EV71 C4a) isolated from a Korean patient. The vaccine candidate was evaluated in mice to determine the vaccination doses and vaccine schedules. BALB/c mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…EV71 vaccine strains used by 3 manufacturers in mainland China belong to subgenotype C4a, while that developed in Taiwan belongs to B4 and that in Singapore to B3 [ 46 ]. The results show that NT antibody induced by a C4a vaccine cross-neutralize EV71 subgenotypes B3, C2, C3, and C5 but not subgenotype A [ 47 ]; the NT antibody induced by a B4 vaccine strongly cross-neutralize B1, B5 and C4a, but poorly neutralize C4b [ 48 ]. The information above demonstrates that the relatedness between the vaccine strain and the circulating strain(s) should be considered for vaccine selection in each country.…”
Section: Discussionmentioning
confidence: 99%
“…EV71 vaccine strains used by 3 manufacturers in mainland China belong to subgenotype C4a, while that developed in Taiwan belongs to B4 and that in Singapore to B3 [ 46 ]. The results show that NT antibody induced by a C4a vaccine cross-neutralize EV71 subgenotypes B3, C2, C3, and C5 but not subgenotype A [ 47 ]; the NT antibody induced by a B4 vaccine strongly cross-neutralize B1, B5 and C4a, but poorly neutralize C4b [ 48 ]. The information above demonstrates that the relatedness between the vaccine strain and the circulating strain(s) should be considered for vaccine selection in each country.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivated vaccines are considered ideal owing to concerns with the potential for vaccine-derived virulent viruses, e.g., from poliovirus attenuated vaccine [ 24 26 ]. In particular, our group recently showed that formalin-inactivated HFMD vaccine using an EV71 strain was a potential candidate vaccine for prevention of EV71 infection [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, many vaccines including inactivated virus vaccines, attenuated live virus vaccines, subunit vaccines, DNA vaccines, and virus-like particle vaccines have been tried. [ 10 11 ] Inactivated virus vaccines are considered advantageous and promising. [ 12 13 ]…”
Section: Introductionmentioning
confidence: 99%